The risk factors of self-destructive behaviours among Malaysian young adults : a preliminary finding - Lim, Yeong Yeong; Pheh, Kai Shuen; Low, Sew Kim (Penerbit Universiti Kebangsaan Malaysia, 2017)
Young adulthood has been identified as the developmental stage with highest suicidal risks in Malaysia. This study aimed to examine the risk factors associated with self-destructive behaviours (i.e. non-suicidal self-injury, suicidal ideation and suicide attempt) among Malaysian young adults. This is a preliminary finding of a survey on 531 university students aged 18 to 25 years old based on a self-reported questionnaire and the General Health Questionnaire – 28(GHQ-28). The prevalence for non-suicidal self-injury, suicidal ideation and suicide attempt was 8.5%,8.4%, 5.8% and 3.6% 3.5% respectively. Further analysis found that severe depression were positively associated with these self-destructive behaviours as well as overall psychological distress. Furthermore, some chronic physical health problems found to be associated with self-destructive behaviours. Insights on the risk factors of self-destructive behaviours among Malaysian youth are crucial in comprehensive mental health management of this alarming problem, as most research rarely focuses on effective measures of treatment and intervention of such behaviours. The findings of the current study may of benefits to policy makers, parents and mental health professional as self-destructive behaviours may be a signal of psychological distress among young adulthood.